Sound Wave Diffraction by a Cavity with Partial_x000D_ Lining - TİRYAKİOĞLU, BURHAN (My University, 2020)
Diffraction of sound wave through a cavity with partial lining is analyzed rigorously. Fourier transformtechnique and Mode Matching method are used to obtain Wiener-Hopf(WH) equation and solution. Thesolution of the problem is found for various problem parameters numerically. The effect of the differentparameters such as the lining length, cavity depth, etc. on the diffraction are illustrated graphically. Theresults are compared numerically with an existing study and found to be consistent.